Quantum heat engine using electromagnetically induced transparency - Zou, Y; Jiang, Y; Mei, Y; Guo, X; Du, S (American Physical Society, 2017)
We report an experiment demonstrating the generation of directional thermal radiation with a spectral brightness that is about 9 times greater than that of the ambient pumping reservoir. The experiment is based on the recent proposal for a nontraditional quantum heat engine and uses cold Rb atoms, electromagnetically induced transparency, and photon correlation spectroscopy [Phys. Rev. A 94, 053859 (2016)].